Exercise intensity and reliability during recreational team handball training for 50–77-year-old unexperienced women - Pereira, Rita; Krustrup, Peter; Castagna, Carlo; Resende, Carlos; Carneiro, Ivone; Magalhães, José; Póvoas, Susana (Biology of Sport, 2024)
This study analyzed the physiological and physical demands of recreational team handbal (RTH) and the training sessions’ (matches) intensity variability in 50–77-year-old postmenopausal women ( n = 20) without prior experience with the sport. Heart rate (HR), blood lactate, rating of perceived exertion (RPE), distance covered, time spent in different locomotor categories, accelerations, decelerations, Player Load (PL), game actions and fun levels were evaluated in 245 matches, played indoor ( n = 130) or outdoor ( n = 115), as small sided games (3×15-min periods). Mean and peak HRs were 79 and 88% of maximal HR (%HR max ), showing reliable values across the training sessions, with time spent in the HR zones showing excellent relative reliability, though poor absolute reliability. Time spent > 80 and > 90%HR max was 48% and 14% of total match time, respectively. Mean and peak blood lactate values were 2.6±0.8 and 2.9±0.9 mmol·l −1 , respectively. RPE was 5.5±1.5, showing good relative though poor absolute reliability, and fun levels were 8.4±1.1 (0–10 scale). Total distance covered was 1878±333 m and the participants spent 54%, 3% and < 1% of total match time walking, fast running and sprinting, respectively. Total PL was 224±41 (AU), with 67% of total match time being spent in low-intensity zones. Participants performed a total of 38 specific high-demanding actions per match, mainly throws (10.6±5.8) and stops (11.0±3.6). RTH training, played as small-sided games, is a high-intensity exercise training mode with high aerobic and anaerobic demands, low RPE and high fun levels for 50–77-year old women without prior experience with the sport. Average cardiovascular demands were consistent across the training sessions.